The Physcomitrella patens exocyst subunit EXO70.3d has distinct roles in growth and development, and is essential for completion of the moss life cycle - Rawat, Anamika; Brejšková, Lucie; Hála, Michal; Cvrčková, Fatima; Žárský, Viktor (The New phytologist, 2017)
The exocyst, an evolutionarily conserved secretory vesicle-tethering complex, spatially controls exocytosis and membrane turnover in fungi, metazoans and plants. The exocyst subunit EXO70 exists in multiple paralogs in land plants, forming three conserved clades with assumed distinct roles. Here we report functional analysis of the first moss exocyst subunit to be studied, Physcomitrella patens PpEXO70.3d (Pp1s97_91V6), from the, as yet, poorly characterized EXO70.3 clade. Following phylogenetic analysis to confirm the presence of three ancestral land plant EXO70 clades outside angiosperms, we prepared and phenotypically characterized loss-of-function Ppexo70.3d mutants and localized PpEXO70.3d in vivo using green fluorescent protein-tagged protein expression. Disruption of PpEXO70.3d caused pleiotropic cell elongation and differentiation defects in protonemata, altered response towards exogenous auxin, increased endogenous IAA concentrations, along with defects in bud and gametophore development. During mid-archegonia development, an abnormal egg cell is formed and subsequently collapses, resulting in mutant sterility. Mutants exhibited altered cell wall and cuticle deposition, as well as compromised cytokinesis, consistent with the protein localization to the cell plate. Despite some functional redundancy allowing survival of moss lacking PpEXO70.3d, this subunit has an essential role in the moss life cycle, indicating sub-functionalization within the moss EXO70 family.
Keywords: Gravitation; Regeneration; mutace; secretory pathway; Cell Proliferation; fylogeneze; Genetic Pleiotropy; Phylogeny; buněčná diferenciace; mechy; EXO70; genetická pleiotropie; Bryopsida; rostlinné proteiny; genový knockout; regenerace; Plant Proteins; Protoplasts; gravitace; pravděpodobnostní funkce; epidermis rostlin; auxin; exocyst; Likelihood Functions; Gene Knockout Techniques; protoplasty; cytokineze; egg cell development; Physcomitrella patens; proliferace buněk; cytokinesis; Mutation; Plant Epidermis; phylogeny; Cell Differentiation; Cytokinesis